Hereditary haematological disorders in the Greek population of Cape Town - Bonafede, R P (Department of Medicine, 2015)
It is a recognized fact that most well defined population groups have their own typical pattern of inherited disorders. The genetic conditions most commonly found in Greek persons are the thalassaemias, glucose-6-dehydrogenase (G-6-PD) deficiency and, to a lesser extent, certain of the haemoglobinopathies. The clinical and socio-economic consequences of these disorders are significant. In the homozygous state, alpha-thalassaemia is incompatible with life, while thalassaemia major (homozygous beta-thalassaemia) results in a severe anaemia with death usually occurring in the second or third decades. Treatment to prolong the life of these patients is very costly. Alpha- and betathalassaemia, when heterozygous, may result in a mild anaemia or be asymptomatic. G-6-PD deficiency results in attacks of haemolysis on ingestion of certain medical preparations and is of far less importance than the thalassaemias. Haemoglobin Sis the commonest haemoglobinopathy occurring in Greeks and results in a severe clinical condition when homozygous, as with the thalassaemias. However, the gene frequency is far less than that of the thalassaemias. The high prevalence of G-6-PD deficiency and haemoglobin Shave been demonstrated to be due to the selective advantage they confer against malaria. This same mechanism probably applies to the thalassaemias but has not been proven. Thus, these disorders have been demonstrated to occur more frequently in low-lying areas and places where malaria was endemic in the past. Population movement has made this situation less clearcut in recent times. Cape Town has a Greek population numbering approximately 5000 persons. As the thalassaemias, particularly, cause a notable public health problem in Greece, it could be expected that the position would be similar, but on a smaller scale in Cape Town. For these reasons it was decided to undertake a study in Cape Town to ascertain exactly what the position was and what recommendations to make concerning management and prevention.